Identity and solidarity in a pluralist society: : A response to Alec Ryrie’s account of Dietrich Bonhoeffer’s legacy - Lenehan, Kevin (Stellenbosch Theological Journal, 2023)
In his recent book Protestants (2017), historian Alec Ryrie argues that while Dietrich Bonhoeffer may have been “the bravest theologian of his generation”, the impact of his prison writings and his opaque vision of a “religionless Christianity” in a world come of age was disastrous for mainstream Protestantism in the United States in the second half of the twentieth century. Ryrie’s analysis of the trajectory of Western liberal Protestantism needs to be nuanced by a more critical and contextual reading of both cultural processes of pluralisation and Bonhoeffer’s prison writings. Still, Ryrie’s sweeping claim goes to the heart of the question about the “usefulness” of Bonhoeffer’s thought and witness for the future of Christian discipleship and engagement in an increasingly post-Christian and multi-religious world. Can Bonhoeffer’s legacy assist Christians to negotiate the delicate balance between identity as disciples of Christ within faith communities and solidarity with people of other faiths or no religion affiliation?